2019
DOI: 10.1021/acs.joc.8b02821
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Catalyzed Iodinations of Carbazoles: Access to Functionalized Carbazoles

Abstract: A copper-catalyzed iodination of carbazoles has been developed. Barluenga’s reagent IPy2BF4 is used to generate a soft electrophilic halonium species for the iodination of the carbazoles. This report represents the first concept of copper-catalyst-promoted electrophilic halogenation of carbazoles. We demonstrated numerous applications of this methodology synthesizing diverse carbazole derivatives, i.e., both electron-rich and electron-deficient systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Some of these aromatic polycyclic compounds are for instance carbazoles including chlorinated and brominated versions and 9H-pyrido [3,4-b]indole [73]. However, halogenation of carbazole is a key subject in medicinal chemistry and materials science and for this reason they are starting materials for the synthesis of numerous bioactive molecules of pharmaceutical importance despite their well-known toxicological characteristics [91]. These nitrogen containing heterocyclic compounds such as the mono-and polyhalogenated carbazoles (PHCZs) which are commonly known as nitrogenated dioxins are suggested to originate from either anthropogenic or natural sources and have been reported to possess toxicities comparable to those of dioxin and furan compounds basically because of their structural similarities [92].…”
Section: Nitrogenated Analogues Of Dioxins Dibenzofurans and Their Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these aromatic polycyclic compounds are for instance carbazoles including chlorinated and brominated versions and 9H-pyrido [3,4-b]indole [73]. However, halogenation of carbazole is a key subject in medicinal chemistry and materials science and for this reason they are starting materials for the synthesis of numerous bioactive molecules of pharmaceutical importance despite their well-known toxicological characteristics [91]. These nitrogen containing heterocyclic compounds such as the mono-and polyhalogenated carbazoles (PHCZs) which are commonly known as nitrogenated dioxins are suggested to originate from either anthropogenic or natural sources and have been reported to possess toxicities comparable to those of dioxin and furan compounds basically because of their structural similarities [92].…”
Section: Nitrogenated Analogues Of Dioxins Dibenzofurans and Their Cmentioning
confidence: 99%
“…Iodine containing versions of polyhalogenated carbazoles are rare in the environment and therefore generally uncommon in natural products and no known study has isolated iodinated carbazoles in the environment at least (2020) 2:1729 | https://doi.org/10.1007/s42452-020-03551-y Review Paper to date [30]. Nonetheless, recent studies have found that iodinated carbazoles are more reactive than chlorinated or brominated carbazoles, and probably more lethal to the biological environment [91].…”
Section: Nitrogenated Analogues Of Dioxins Dibenzofurans and Their Cmentioning
confidence: 99%
“…Recently, new reports about effective, mild and safe iodination procedures emerged for arenes (Espuña et al 2004;Barluenga et al 2007;Racys et al 2016) and heterocycles (Barluenga et al 1993;Hamri et al 2012;Przypis and Walczak 2019). In this subject, hypervalent iodine reagents have been at the forefront of synthetic methodology developments in the past 20 years (Merritt and Olofsson 2009;Yoshimura and Zhdankin 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this subject, hypervalent iodine reagents have been at the forefront of synthetic methodology developments in the past 20 years (Merritt and Olofsson 2009;Yoshimura and Zhdankin 2016). Multiple examples of iodonium salt usage in organic synthesis have been reported in recent literature (Barluenga et al 1993;Espuña et al 2004;Hamri et al 2012;Borzenko et al 2015;Racys et al 2016;Iskra and Murphree 2017;Liu et al 2017;Przypis and Walczak 2019). Aryliodonium and diaryliodonium salts play a special role in this field because they are air-and moisture stable and soluble in many organic solvents despite their reactive framework.…”
Section: Introductionmentioning
confidence: 99%
“…[4a] In the same year Ma reported the synthesis of carbazoles via Au(III)-catalyzed cyclization of 1-(indol-2-yl)-3-alkyn-1-ols, [4b] while we have recently described the gold-catalyzed intramolecular 1,3-iodine transfer reaction in (3-iodoindol-2-yl)butynols for the synthesis of polyfunctionalized carbazoles (Scheme 1b). [5] Taking into account that the above iodine migration as well as the direct iodination of the carbazole nucleus occurred at the C3 position, [6] the discovery of new protocols for the controlled preparation of iodinated carbazoles at different positions is challenging. Despite the significant progress attained in this area, the reported protocols suffer from drawbacks such as the necessity of preparation of sophisticated precursors.…”
mentioning
confidence: 99%